Persepsi Pengajar dan Pembelajar Bahasa Inggris Terhadap Penggunaan Artificial Intelligence (AI) untuk Literary Writing - Suharto, Ririn Pratiwi; Maulana, Andi Reza (TRANSFORMATIKA, 2024)
Literary Writing focuses on writing literary works, such as poetry, drama, short stories and other types of literary writing. The practice of writing Literary Writing provides an experience that is not easy for English language learners. This research is a case study with the research subjects being English teachers and learners. Research data was taken from the results of the questionnaire. This research aims to identify the use of Artificial Intelligence (AI) for learning Literary Writing as seen from the perceptions of English language teachers and learners. The research results show that Artificial Intelligence (AI) helps English teachers to prepare learning plans and materials, create an interactive and  attractive learning atmosphere, and evaluate Literary Writing learning outcomes. Furthermore, research shows that the use of Artificial Intelligence (AI) for English learners is useful for developing ideas and improving writing skills, correcting English grammatical errors, and enriching vocabulary. Apart from that, there is a negative side to using Artificial Intelligence (AI), namely dependency which limits creativity and critical thinking skills for English language learners. Thus, English teachers must monitor the use of Artificial Intelligence (AI) when used in classroom learning activities.